1996
DOI: 10.1084/jem.184.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a nuclease-resistant decoy RNA that selectively blocks autoantibody binding to insulin receptors on human lymphocytes.

Abstract: SummaryAn RNA containing 2'-amino pyrimidines has been isolated using in vitro selection techniques that specifically and avidly (apparent Ka ,'-,30 nM) binds a mouse monoclonal antibody called MA20. This 2'-amino-derivatized RNA is at least 10,000-fold more stable than unmodified RNA in serum, and can act as a decoy and block MA20 binding to its natural antigen, the human insulin receptor, on lymphocytes. Furthermore, this RNA decoy can inhibit MA20-mediated downmodulation of insulin receptor expression on hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…SE RNAs were internally radiolabeled and isolated as described Sullenger 1996, 1997;Bae et al 2002). Purified RNAs were incubated with proteins as described above.…”
Section: Binding Analysis Of Selected Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…SE RNAs were internally radiolabeled and isolated as described Sullenger 1996, 1997;Bae et al 2002). Purified RNAs were incubated with proteins as described above.…”
Section: Binding Analysis Of Selected Rnasmentioning
confidence: 99%
“…In vitro selection was carried out essentially as described previously Sullenger 1996, 1997;Bae et al 2002), with a few modifications. A random pool of RNA oligonucleotides was produced by in vitro transcription of synthetic DNA templates with NTPs and T7 RNA polymerase.…”
Section: Selection Proceduresmentioning
confidence: 99%
“…In vitro (12) 30 Doudna et al, 1995;Lee and Sullenger, 1996 Monoclonal antibody to acetylcholine receptor RNA In vitro (12 +12 more) 6-60 Lee and Sullenger, 1997;Seo and Lee, 2000;Hwang and Lee, 2002 Immunoglobulin E…”
Section: Rnamentioning
confidence: 99%
“…In order to develop an RNA aptamer against MA20 that was nuclease resistant, a 2l-aminopyrimidine-modified RNA selection was conducted on MA20 (Lee and Sullenger, 1996). After 12 rounds of SELEX, a modified RNA aptamer was identified that bound to MA20 with a K d of 30 nmol/L.…”
Section: Factor Ixamentioning
confidence: 99%
See 1 more Smart Citation